Community Business Action Plan Based on Regional Potential in The Framework of Agrarian Reform - Aristiono Nugroho (Pusat Publikasi Nusantara, 2023)
Sentang Village, Wonogiri District, Wonogiri Regency needs a community business action plan based on regional potential within the framework of agrarian reform. The action plan contains a plan of activities that need to be carried out by the village government, to develop community businesses within the framework of agrarian reform, for the improvement of community welfare. This research uses qualitative research methods, with a rationalistic approach. The number of informants was 10, purposively selected. The data consists of: (1) Primary data, obtained from interviews with informants; (2) Secondary data, in the form of population data in Sentang Village. Meanwhile, data analysis is carried out by utilizing qualitative data analysis techniques. The results of this study show that the action plan is prepared by taking into account physical and non-physical potentials, as well as the economic contribution of business fields in Sentang Village, which include: (1) agricultural business, (2) livestock business, (3) fisheries business, (4) trading business, (5) handicraft business, and (6) tourism business. Action plan provides benefits in the form of community welfare, consisting of: (1) economic welfare, (2) psychological welfare, (3) social welfare, and (4) cultural welfare